Conditional KIAA1549:BRAF mice reveal brain region‐ and cell type‐specific effects. Issue 10 (16th August 2013) - Kaul, Aparna; Chen, Yi‐Hsien; Emnett, Ryan J.; Gianino, Scott M.; Gutmann, David H.
Summary Low‐grade brain tumors (pilocytic astrocytomas) that result from a genomic rearrangement in which the BRAF kinase domain is fused to the amino terminal of the KIAA1549 gene (KIAA1549:BRAF fusion; f‐BRAF) commonly arise in the cerebellum of young children. To model this temporal and spatial specificity in mice, we generated conditional KIAA1549:BRAF strains that coexpresses green fluorescent protein (GFP). Although both primary astrocytes and neural stem cells (NSCs) from these mice express f‐BRAF and GFP as well as exhibit increased MEK activity, only f‐BRAF‐expressing NSCs exhibit increased proliferation in vitro. Using Cre driver lines in which KIAA1549:BRAF expression was directed to NSCs (f‐BRAF; BLBP‐Cre mice), astrocytes (f‐BRAF; GFAP‐Cre mice), and NG2 progenitor cells (f‐BRAF; NG2‐Cre mice), increased glial cell numbers were observed only in the cerebellum of f‐BRAF; BLBP‐Cre mice in vivo. The availability of this unique KIAA1549:BRAF conditional transgenic mouse strain will enable future mechanistic studies aimed at defining the developmentally–regulated temporal and spatial determinants that underlie low‐grade astrocytoma formation in children. genesis 51:708–716. © 2013 Wiley Periodicals, Inc.